Busy Book: Educational Tool to Enhance Language Skills in Early Childhood Education - Yanti, Ni Made Riska; Ambara, Didith Pramunditya (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Children often face challenges in learning new material, requiring teachers to develop appropriate instructional media to support the learning process. This study aims to develop a busy book as an educational medium to stimulate children’s language development. The research employed the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The product was evaluated by one content expert, one instructional design expert, and one media expert, involving three children in individual trials, five children in small group trials, and 19 children in effectiveness testing. Data were collected through questionnaires and non-test observations, with data analysis conducted using inferential statistics and quantitative descriptive analysis. Expert evaluations revealed that the instructional design scored 88.88% (classified as good), instructional media 95.83% (very good), individual trials 94.16% (very good), and small group trials 92.5% (very good). The product design scored 90.90% (very good). Effectiveness testing indicated a significant impact, with tstatistics > ttable (12.325 > 1.734). These findings suggest that the busy book is a feasible and effective educational medium for stimulating language skills in Group B children.